Controlled precipitation of lithium disilicate (Li2Si2O5) and lithium niobate (LiNbO3) or lithium tantalate (LiTaO3) in glass-ceramics. Issue 1 (January 2018) - Dittmer, Marc; Ritzberger, Christian; Höland, Wolfram; Rampf, Markus
Abstract: In the present study, the crystallization principles and phenomena of base glasses from the system of SiO2 -Li2 O-P2 O5 -Al2 O3 -K2 O-Nb2 O5 or Ta2 O5 were investigated. Annealing parameters such as temperature and time were varied. Annealing the base glasses 10 min at temperatures <850 °C for Nb2 O5 or Ta2 O5 containing samples lead to the crystallization of Li2 SiO3 . At higher annealing temperatures or longer annealing times, Li2 SiO3 disappeared and Li2 Si2 O5 was the main crystal phase in all glass-ceramics. After the dissolution of Li2 SiO3, the minor crystal phases of LiNbO3 or LiTaO3 were precipitated. Increasing the annealing temperatures as well as the annealing times lead to higher bending strengths up to about 676 MPa and CR-values of up to 100. Increasing the contents of Nb2 O5 or Ta2 O5 lead to higher CR-values. The radiopacities increased up to 355% compared to aluminum.